Using agent-based technology to create a cost effective, integrated, multimedia view of the electronic medical record. - Lowe, H. J. (American Medical Informatics Association, 1995)
Image Engine is multi-user, client-server database for the storage, retrieval and sharing of a wide range of digitized biomedical images under development at the University of Pittsburgh. This paper provides an overview of the system and describes the use of agent-based technology to integrate clinical information from the Image Engine database and the MARS clinical information system at the University of Pittsburgh Medical Center. Agent-mediated links provide a mechanism for combining clinical data from multiple databases to create a unified, multimedia view of the electronic medical record.